2013
DOI: 10.1016/j.rboe.2012.06.006
|View full text |Cite
|
Sign up to set email alerts
|

Proximal iliotibial band syndrome: case report

Abstract: Objective The overuse injuries in the hip joint occur commonly in sports practitioners and currently due to technical advances in diagnostic imaging, especially magnetic resonance imaging (MRI), are often misdiagnosed. Recently, a group of people were reported, all female, with pain and swelling in the pelvic region. T2-weighted MRI showed increased signal in the enthesis of the iliotibial band (ITB) along the lower border of the iliac tubercle. We report a case of a 34 year old woman, non-professio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
21
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(29 citation statements)
references
References 10 publications
(13 reference statements)
1
21
0
Order By: Relevance
“…It usually occurs in long-distance runners, cyclists, and football players and represents the most common cause of lateral knee pain in runners [1].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…It usually occurs in long-distance runners, cyclists, and football players and represents the most common cause of lateral knee pain in runners [1].…”
Section: Discussionmentioning
confidence: 99%
“…Hip joint overload injuries usually occur in sports practitioners, and presently, because of advances in diagnostic imaging tests, principally MRI, they are often diagnosed [1,2]. Sher et al [1] studied group patients referring pain and edema in the region of the iliac tubercle and demonstrated that T2-weighted MRI shows an increase in the iliotibial band (ITB) signal along the lower border of the iliac tubercle.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations